PROPOSED MARKETING STRATEGY FOR HOTEL BUSINESS AT INTEGRATED BUILDING SOEKARNO HATTA AIRPORT - Andini, Rizky
PT Angkasa Pura II (Persero) through PT Angkasa Pura Propertindo as a subsidiary is currently in the construction phase of a hotel located in the Integrated Building area of Soekarno Hatta Airport. This activity as one of the company’s efforts in business development an to increase non-aero revenue to achieve the 11.4T revenue target by developing support from subsidiaries.